2014
DOI: 10.1080/10426914.2013.852211
|View full text |Cite
|
Sign up to set email alerts
|

Study of Surface Properties in Particulate-Reinforced Metal Matrix Composites (MMCs) Using Powder-Mixed Electrical Discharge Machining (EDM)

Abstract: This article investigates the surface modification of three different types of metal matrix composites (MMCs) 65vol%SiC/A356.2, 10vol% SiC-5vol% quartz/Al, and 30vol%SiC/A359 using powder-mixed electrical discharge machining (PMEDM) process. Microhardness and surface integrity were evaluated after each trial, and contributing process parameters were identified. It was found that microhardness increased primarily with increase in the density of reinforced particles in the matrix. Each workpiece was examined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(32 citation statements)
references
References 15 publications
0
29
0
3
Order By: Relevance
“…In order to prevent the formation of surface cracks, high roughness and thick recast layer during EDM, number of advancements in EDM process has been employed by many Downloaded by [George Mason University] at 06: 41 22 June 2016 researchers such as Ultrasonic Vibration Assisted EDM (UVAEDM) [20], Rotary Assisted EDM (RAEDM) [21], HyFlex EDM [22], Electro Discharge Coating/surface modification by composite or green tool electrode [23][24][25][26][27][28], Near Dry EDM [29] and Powder Mixed EDM (PMEDM) [30][31][32][33][34][35][36]. Among them, PMEDM has been considered the most promising approach to enhance the surface quality by reducing surface crack density [37].…”
mentioning
confidence: 99%
“…In order to prevent the formation of surface cracks, high roughness and thick recast layer during EDM, number of advancements in EDM process has been employed by many Downloaded by [George Mason University] at 06: 41 22 June 2016 researchers such as Ultrasonic Vibration Assisted EDM (UVAEDM) [20], Rotary Assisted EDM (RAEDM) [21], HyFlex EDM [22], Electro Discharge Coating/surface modification by composite or green tool electrode [23][24][25][26][27][28], Near Dry EDM [29] and Powder Mixed EDM (PMEDM) [30][31][32][33][34][35][36]. Among them, PMEDM has been considered the most promising approach to enhance the surface quality by reducing surface crack density [37].…”
mentioning
confidence: 99%
“…In the field of die sinking EDM, many investigations have been carried out using metal powder additives in dielectric medium to improve the MRR and surface characteristics. Conductive metal powder reduces the dielectric strength of the fluid and thereby increases the spark energy across the two electrodes, thus, enhances the stability of the process and improves the performance measures (Kansal et al, 2005;Sidhu et al, 2014). As per the literature available, no research work found on powder mixed dielectric in WEDM.…”
Section: Literature and Motivation For Present Workmentioning
confidence: 99%
“…Due to its lightweight Aluminum composite also has a huge application in automobile sector but due to its low melting point and low strength its use has been restricted to that component which has an application of high heat treatment areas. Many researchers found [1][2][3] Silicon Carbide/Silicon Nitride are very suitable ceramic composites which could raise the strength and thermo-physical composite properties but due to their high sintering temperature its difficult to fabricate. SiC either in particle or in whisker form can be added within the Al-A359 composites by P/M route.…”
Section: Introductionmentioning
confidence: 99%